Smart training with dumbbells - Mannie, K. (Scholastic Coach & Athletic Director, 2006)
Even though the fire-storm on free weights vs. machines rages on, one undeniable fact continues to emerge from the ashes: Dumbbells (DBs) offer an effective, relatively safe, and very smart training mode across a broad range of applications.